Insomnia and Information and Communication Technologies (ICT) in Elderly People: A Systematic Review - Arianna Salvemini; Grazia D’Onofrio; Filomena Ciccone; Antonella Greco; Anita Tullio; Filomena Addante; Daniele Sancarlo; Gianluigi Vendemiale; Gaetano Serviddio; Francesco Ricciardi; Francesco Giuliani; Antonio Greco (Medical Sciences, 2019)
Background: Insomnia seems to be related to disability, risk of injury, metabolic syndrome, risk for cardiovascular diseases, cognitive impairment, depression and impaired quality of life. Objectives: The goals in this paper was (1) to keep track of technological concepts and approaches to improve insomnia in elderly people, and (2) to define the effect that information and communication technologies (ICT) is having on patients’ care. Design: A systematic review was conducted from existing literature. Our selection criteria included: (1) age ≥ 60 years; (2) diagnosis of insomnia with the International Classification of Sleep Disorders (ICSD-II), (3) CBTi (cognitive behavioural therapy insomnia), (4) use of technological tools, and (5) associations between insomnia-related variables and indices of disability, quality of life, and global clinical assessments. Data analysis: 11 articles were included. An inductive content analysis was used for data extraction. Results: Our review revealed any technological systems that could purportedly rehabilitate elderly patients with insomnia. Three categories of research were identified from the review: (1) Internet Deliver-CBTi, (2) virtual coaches, and (3) sleep technologies. Conclusions: The potential for ICT to support insomnia care at home can improve the quality of life for families and reduce health care costs and premature institutional care.